2006
DOI: 10.1097/01.pgp.0000185410.39050.ac
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin Promotes Ovarian Carcinoma Cell Invasion and Its Retained Expression Predicts Poor Prognosis in Ovarian Carcinoma

Abstract: The majority of patients diagnosed with ovarian carcinoma are classified as being in advanced stage of disease. In a situation of cancer spread throughout the abdominal cavity, a successful curative treatment is difficult to achieve. Therefore, preventing binding of tumor cells to the mesothelium is crucial for patients' outcome. One important mechanism is the interaction between hyaluronic acid and the CD44 receptor with its submembrane linking complex. This consists of ezrin, radixin, and moesin and connects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 17 publications
4
39
0
Order By: Relevance
“…Some studies showed that high expression of Ezrin might be correlated with the invasion of different tumours. [18][19][20][21][22] However, some investigators suggested that Ezrin gene might be a tumour suppressor, inhibiting tumour development. Others proposed that the location of Ezrin protein in cells migrated with the occurrence and development of tumour, but the total amount of Ezrin protein showed no change.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that high expression of Ezrin might be correlated with the invasion of different tumours. [18][19][20][21][22] However, some investigators suggested that Ezrin gene might be a tumour suppressor, inhibiting tumour development. Others proposed that the location of Ezrin protein in cells migrated with the occurrence and development of tumour, but the total amount of Ezrin protein showed no change.…”
Section: Discussionmentioning
confidence: 99%
“…All histologic slides were re-evaluated by two pathologists (E. Gradhand and S. Hauptmann) using a multihead microscope. Tumor patients and tissue samples were, in part, described elsewhere (28). Histology was classified according to the WHO, and grading was assessed according to Silverberg (29).…”
Section: Methodsmentioning
confidence: 99%
“…and S.H.). Tumor patients and tissue samples were in part described elsewhere (6,20). Additional 49 samples from ovarian carcinoma patients were provided by the Tumor Bank Ovarian Cancer (TOC), Department of Gynecology and Obstetrics of the Charit e (Berlin, Germany).…”
Section: Patient Population and Clinical Datamentioning
confidence: 99%